New Xerophilic Species of Penicillium from Soil - Rodríguez-Andrade, Ernesto (J Fungi (Basel), 2021)
Soil is one of the main reservoirs of fungi. The aim of this study was to study the richness of ascomycetes in a set of soil samples from Mexico and Spain. Fungi were isolated after 2% w/v phenol treatment of samples. In that way, several strains of the genus Penicillium were recovered. A phylogenetic analysis based on internal transcribed spacer (ITS), beta-tubulin (BenA), calmodulin (CaM), and RNA polymerase II subunit 2 gene (rpb2) sequences showed that four of these strains had not been described before. Penicillium melanosporum produces monoverticillate conidiophores and brownish conidia covered by an ornate brown sheath. Penicillium michoacanense and Penicillium siccitolerans produce sclerotia, and their asexual morph is similar to species in the section Aspergilloides (despite all of them pertaining to section Lanata-Divaricata). P. michoacanense differs from P. siccitolerans in having thick-walled peridial cells (thin-walled in P. siccitolerans). Penicillium sexuale differs from Penicillium cryptum in the section Crypta because it does not produce an asexual morph. Its ascostromata have a peridium composed of thick-walled polygonal cells, and its ascospores are broadly lenticular with two equatorial ridges widely separated by a furrow. All four new species are xerophilic. Despite the genus Penicillium containing more than 480 known species, they are rarely reported as xerophilic.